Evaluating the Influence of Missing Data on Classification Algorithms in Data Mining Applications - Blomberg, Luciano C.; Ruiz, Duncan Dubugras A. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2013: Anais do IX Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2013.5736, 2013)
This paper presents an analysis regarding the influence of missing data on datasets when submitted to traditional classification algorithms in data mining applications. For this purpose, we use ten UCI datasets and manipulate them to hold controlled levels of missing data. Our empirical analysis shows that the classification performance decreases after significant insertion of missing values in all datasets tested. Among the analyzed algorithms, Naïve Bayes is the least influenced by missing data, being SMO the next. IBK is the most influenced, presenting the lowest accuracy, predominantly in datasets whose independent variables are continuous.